The EFFECT OF JUMP TO BOX EXERCISES AS HIGH 30 CM AND 40 CM ON THE LEG MUSCLES POWER VOLLEYBALL PLAYERS GOVITA SEMARANG - Putri, Yahra Nabella; Soegiyanto, Soegiyanto (Department of Sports Science, Faculty of Sports Science, Universitas Negeri Semarang, 2021)
The purpose of this study: 1) To find out the effect of jump to box exercise as high 30 cm on leg muscle power of Govita Volleyball Players Semarang, 2) To find out the effect of jump to box exercise as high 40 cm on leg muscle power of Govita Volleyball Players Semarang, 3) To find out the difference effect of jump to box exercise as high 30 cm and 40 cm on leg muscle power of Govita Semarang Volleyball Player. This research is using 16 women volleyball players Govita Semarang with range on age 13-15 years to be sample. The research design using a match subject design, the group division using the subject matched ordinal pairing formula A-B-B-A. Test instrument used a vertical jump test with a vertical board. Data analysis use a pair sample t-test to test the hypothesis. The results of this study: 1) There have an effect of jump to box exercise as high 30 cm on leg muscle power of Govita Semarang Volleyball Player with the result tcount (3,989) > ttable (2,364), 2) There have an effect of jump to box exercise as high 40 cm on leg muscle power of the Govita Semarang Volleyball Player with the result tcount (4,518) > ttable (2,364) , 3) Both result have same effect of leg muscle power of the Govita Volleyball Players Semarang, with difference result tcount (1,432) < ttable (2,364). The conclusions are: 1) There have an effect of 30 cm high jump to box exercise on leg muscle power of Govita Volleyball players in Semarang, 2) There have an effect of 40 cm high jump to box exercise on the leg muscle power of the Govita Volleyball players in Semarang, 3) Both exercises have the same effect on the results of the leg muscle power of the Govita Volleyball players in Semarang. For the future researchers who isinterested to do the same research, they can adding a control group comparison.